2018
DOI: 10.1016/j.clnu.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of energy and protein adequacy with 60-day mortality in mechanically ventilated critically ill patients: A prospective observational study

Abstract: Energy and protein adequacy of ≥2/3 of the prescribed amounts were associated with a trend towards increased 60-day mortality among mechanically ventilated critically ill patients. However, neither energy nor protein adequacy alone at ≥ or <2/3 adequacy affect 60-day mortality. Increased mortality was associated with provision of energy and protein at ≥2/3 of the prescribed amounts, which only affected patients with low nutritional risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 26 publications
5
36
3
1
Order By: Relevance
“…Although we do not have strong data about improved mortality outcomes, observational studies have suggested that full enteral feedings are associated with improved outcomes in nutritionally high-risk critically ill patients. 53,54,96 This again emphasizes the fact that baseline nutrition status of patients is a strong predictor for clinical outcomes in nutrition studies.…”
Section: Protein or Energy Dilemma: Optimization Is The Keymentioning
confidence: 96%
“…Although we do not have strong data about improved mortality outcomes, observational studies have suggested that full enteral feedings are associated with improved outcomes in nutritionally high-risk critically ill patients. 53,54,96 This again emphasizes the fact that baseline nutrition status of patients is a strong predictor for clinical outcomes in nutrition studies.…”
Section: Protein or Energy Dilemma: Optimization Is The Keymentioning
confidence: 96%
“…25 Jeejeebhoy pointed out that lower rates of nutrient provision have frequently been associated with better clinical outcomes in critically ill patients. 17,18,50,51 But many other studies have found the opposite: that patients who received more nutrients had better clinical outcomes. 17,[52][53][54][55][56][57][58] Both conclusions can't be correct, or they are correct in different situations.…”
Section: Permissive Underfeeding and Clinical Outcomesmentioning
confidence: 97%
“…The NUTRIC score was developed in studies of critically ill patient populations and has been validated in many observational studies from different countries. 11,[14][15][16][17][18][19][20][21][22][23] As IL-6 is not routinely performed in most ICUs in the world, the modified-NUTRIC (mNUTRIC) score without IL-6 was proposed and revalidated. 14 However, one of the major limitations of the NUTRIC/mNUTRIC score is the absence of classical nutrition variables such as recent food intake and weight change.…”
Section: Nutrition Risk Screeningmentioning
confidence: 99%
“…11,[14][15][16][20][21][22][23] Various observational studies in different populations have also shown that clinical outcomes are modified by nutrition adequacy depending on the risk status of the patients (Table 1). 11,14,[16][17][18][19] The NUTRIC/mNUTRIC score remains to be prospectively tested in a randomized controlled trial. There have been inconsistent results from post hoc analyses of prospective randomized trials.…”
Section: Nutrition Risk Screeningmentioning
confidence: 99%